Sistem Pendukung Keputusan Pemberian Bantuan Bedah Rumah Dengan SAW Pada Dinas PUPR Provinsi Jambi - Rahmawati, Sri; Jasmir, Jasmir (Jurnal Manajemen Sistem Informasi, 2023)
The increase in the number of house renovations at the Jambi Provincial PUPR Office from year to year has caused PPTK delays in determining prospective beneficiaries. For that we need a system that can support the decisions taken. The Decision Support System provides facilities to conduct analysis so that the decision-making process carried out by the PUPR Office of Jambi Province can be of higher quality. This study uses the SAW method and UML (Unified Modeling Language) modeling tools with the diagrams used include Use Case Diagrams, class diagrams, activity diagrams and this research produces a prototype that can be implemented further so as to produce a decision support system for home surgery assistance. at the PUPR Office of Jambi Province.